1977
DOI: 10.1243/emed_jour_1977_006_011_02
|View full text |Cite
|
Sign up to set email alerts
|

A Flow Visualization Study of Prosthetic Aortic and Mitral Heart Valves in a Model of the Aorta and Left Heart

Abstract: An in vitro flow visualization study has been carried out on a range of aortic and mitral valve prostheses mounted in rigid, transparent models of the aorta and left ventricle. The valves were subjected to pulsatile flow and the flow patterns produced by each valve were visualized by injecting multi-dye streams into the valve orifice, or by observing illuminated particles suspended in the flow. The patterns were recorded by still photography and high speed cinematography.In the mitral region each tilting disc … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
2

Year Published

1977
1977
1992
1992

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 6 publications
0
2
0
2
Order By: Relevance
“…The reflux level was found to be higher than desirable, but this should not cause clinically significant insufficiency except in patients with low cardiac stroke volumes. The opening and closing characteristics were unremarkable, and the flow patterns produced by the valve in the model ventricle were similar to those produced by two tilting disc valves (Wright, 1977). The design features of the new valve should overcome two of the problems associated with the early model, for accelerated wear studies have shown the expected life to be at least five times that of the former valve (Abrams, 1976), and the thickened and reshaped hooks ensure adequate retention of the flap in the orifice.…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…The reflux level was found to be higher than desirable, but this should not cause clinically significant insufficiency except in patients with low cardiac stroke volumes. The opening and closing characteristics were unremarkable, and the flow patterns produced by the valve in the model ventricle were similar to those produced by two tilting disc valves (Wright, 1977). The design features of the new valve should overcome two of the problems associated with the early model, for accelerated wear studies have shown the expected life to be at least five times that of the former valve (Abrams, 1976), and the thickened and reshaped hooks ensure adequate retention of the flap in the orifice.…”
Section: Resultsmentioning
confidence: 70%
“…The camera shutter was electrically released by a cam-driven microswitch actuated from the test rig drive shaft, and the cam was adjusted so that photographs were taken at chosen portions of the simulated diastolic filling cycle. Full details of the techniques usedt together with results from a number of aortic and mitral valve prostheses are given by Wright (1977). Figure 3 shows the variation of mean diastolic pressure gradient with mean diastolic flow rate.…”
Section: Methodsmentioning
confidence: 99%
“…l Einleitung heute vorwiegend eingesetzt werden, ist ihre Unnatur-Der Ersatz einer defekten natürlichen Herzklappe liehe Flußführung und die daraus resultierenden Wirdurch eine künstliche ist heute eine Routineoperation, belbüdungen, Strömungsseparationen und -wiederderen Ergebnis für den Patienten eine neue Lebens-anlagerungen, Totwassergebiete u. a. m. [7,13,14]. qualitätdarstelltDaalsFolgederlmplantationenaber Zuf Untersuch der strömungen wer den mehrere noch immer 2 bis 5% der Patienten sterben [1], wird Technikenangewendet>2 .…”
unclassified
“…Sichtbarmachung [9,13]. Die Sichtbarmachung ist eine Das Hauptproblem der mechanischen Klappen, die einfache Methode, um einen Überblick über die Strö-Brought to you by | University of Arizona Authenticated Download Date | 7/23/15 4:05 AM Biomedizinische Technik Band 36 Heft 7-8/1991 Sichtbarmachung stationärer Strömungen hinter künstlichen Herzklappen 163 mung zu erhalten und gezielt die Gebiete auszusuchen, die für eine nähere Untersuchung interessant sind.…”
unclassified